(untitled) (African Journal of Biomedical Research, 2020)
Risky sexual behaviours increase the likelihood of contracting sexually transmitted diseases. Undergraduates are peculiarly at a high risk of exposure to risky sexual behaviours because many are becoming free from parental influences and monitoring for the first time in life as well as peer pressures. This study examined the prevalence of risky sexual behaviour and the experience of sexual coercion among clinical students of the College of Medicine, University of Ibadan, Nigeria. This was a descriptive cross-sectional study carried out among 300 level to 600 level clinical students of the College of Medicine, University of Ibadan using a self-administered questionnaire. There were 399 participants. The male-female distribution was 52.1% and 47.9% respectively. 84.4% fell within the 20 to 24 age range (mean age of 22.88±2.2). 18% were sexually active, 65% have had at least two sexual partners. Less than half (47%) reported inconsistent condom use while 77% had ever had unprotected sex; 41.9% of females had experienced at least one form of sexual coercion. Gender [p = <0.001, OR (95% CI) = 0.40 (0.26, 0.63)] and department [p=0.003, OR (95% CI) =0.41 (0.23, 0.75)] were found to be significant in predicting experience of sexual coercion. There was a high prevalence of risky sexual behaviour among the sexually active students. In addition, about one-third of all the students who responded to the questionnaire reported an experience of sexual coercion. Hence there is a need to implement sexual and reproductive health interventions in this and similar populations